THE ECONOMIC IMPACT OF THE COVID-19 OUTBREAK: EVIDENCE FROM INDONESIA - Pitaloka, Herninda; Al Umar, Ahmad Ulil Albab; Hartati, Eka Resmi; Fitria, Dessy (Univesitas Muhammadiyah Malang, 2020)
This research aims to analyses the economic impact of the COVID-19 outbreak on the stock market in Indonesia. This research is a quantitative descriptive study by collecting various sources from journals and current case studies about the COVID-19 outbreak. The technique of collecting data uses quotations and related news. The results in this study are The COVID-19 pandemic outbreak harms the capital market, where the occurrence of this pandemic has affected many investors in making investment actions that are very influential on the IHSG.